The effect of the knowledge index on the community literacy development index and the level of reading interest: A case study in West Java in 2024 - Sihombing, Pardomuan Robinson; Arsani, Ade Marsinta; Huda, Miftahul; Ahmaddien, Iskandar; Aji, Lexi Jalu (Priviet Social Sciences Journal, 2025)
This study examines the reciprocal relationships between the Knowledge Index (KI), the Community Literacy Development Index (CLDI), and the Level of Reading Interest (LRI) across 27 districts/cities in West Java (2024). Using a quantitative design with Partial Least Squares–Structural Equation Modeling and a conditional process perspective, we test direct and feedback effects among the three constructs. Descriptive statistics indicate substantial variation in literacy development and reading interest across regions. Model fit indices exceed conventional thresholds, supporting the adequacy of the specified structure. The results show that KI has a significant positive effect on both CLDI and LRI, indicating that accumulated schooling and knowledge capital translate into stronger literacy ecosystems and more active reading behaviors. Conversely, both CLDI and LRI exert significant positive effects on KI, evidencing a reinforcing cycle in which richer literacy environments and higher reading engagement further elevate knowledge attainment. These findings highlight a virtuous, bidirectional dynamic: knowledge deepens literacy and reading, while literacy investment and reading practice amplify knowledge. Policy implications include prioritizing integrated literacy programs across the life course, leveraging digital access, and coordinating libraries, schools, and local governments to simultaneously lift ecosystem quality and individual reading practices. The study provides actionable evidence for place-based literacy policy and human capital formation in emerging regions.